Analysis of safety talks or safety communication in industry: a literature review - Hakim, Abdurrohman; Hariyono, Widodo; Solikhah, Solikhah (Jurnal EduHealth, 2024)
Improving safe and healthy working conditions is a must, with an emphasis on identifying and mitigating workplace hazards. Safety Communication or Safety Talk plays a key role in preventing work accidents and increasing workers' understanding of Occupational Safety and Health (K3). This research focuses on the analysis of Safety Talk or Safety Communication in industry as a response to the urgency of occupational health and safety. In a systematic review, applying the PRISMA method to search and analyze recent papers (2018-2023) on Safety Talk or Safety Communication in various search engines, including Google Scholar and Pubmed. Eligibility criteria and a review process were used to select 7 high-quality articles, and Mendeley was used for reference management. The research results confirm the important role of safety communications in improving compliance and performance in various industries. A positive relationship was seen between safety discussions, PPE compliance, and PPE understanding. Safety cultures vary across the construction industry, and climate and crew cohesion support safety communication. Safety messages via text messages were successful in increasing supervisor compliance. Safety communication mediates the relationship between safety culture and performance in the petrochemical industry. Conclusions emphasize expanding safety communication efforts to strengthen safety culture and improve performance in the work environment.